"Soft on rigid" nanohybrid as the self-supporting multifunctional cathode electrocatalyst for high-performance lithium-polysulfide batteries. (December 2020) - Wang, Jiayi; Luo, Dan; Li, Junhua; Zhang, Yongguang; Zhao, Yan; Zhou, Guofu; Shui, Lingling; Chen, Zhongwei; Wang, Xin
Abstract: Lithium-sulfur (Li–S) batteries have been deemed as next-generation large-scale energy storage devices. However, the severe shuttle effect and sluggish conversion kinetics of lithium polysulfides significantly impede the commercialization of Li–S batteries. Herein, a unique "soft on rigid" composite consist of oxygen-deficient and Co cluster-decorated TiO2 nanofibers with carbon nanofibers (CNF), embedding numerous Co nanoparticles (denoted as "Co–TiO2-x /CNF") is developed as a high-performance self-supporting multifunctional cathode electrocatalyst. The Co–TiO2-x /CNF offers vast surface area and enlarged porosity to homogenize sulfur distribution and enhance sulfur immobilization. The oxygen deficient Co–TiO2-x fiber and CNF establish a three-dimensional conductive framework, which accelerates electron and ion transportation within the electrode. Meanwhile, the introduction of Co clusters significantly regulate the Ti d-band center and thereby improving the Li2 S6 adsorbability. Benefiting from these synergistic features, the Li2 S6 /Co–TiO2-x /CNF electrode delivers outstanding cycling stability (capacity fading rate of 0.03% per cycle over 500 cycles) and an improved rate capability (743 mAh g −1 at 3.0C). This design strategy based on synergy engineering could also open up new possibilities for the practical application of high performance Li–S batteries and promote the material design in related energy storage fields. Graphical abstract: Long-term operation of Li2 S6 /Co–TiO2-x /CNF cathode and its typical SEM image with reaction mechanism. Image 1 Highlights: A unique "soft on rigid" composite is developed as a high-performance multifunctional cathode electrocatalyst. The introduced oxygen vacancies and Co cluster synergistically altered the d band center of Ti atoms. The obtained Li2 S6 /Co-TiO2-x /CNF cathode enables outstanding cycling stability and improved rate capability.